2016
DOI: 10.1097/md.0000000000002443
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Predictors of Long-term Success in Ultrasound-guided High-intensity Focused Ultrasound Ablation Treatment for Adenomyosis

Abstract: The long-term outcomes of ultrasound-guided high-intensity focused ultrasound (USgHIFU) ablation treatment for adenomyosis and the relevant factors affecting the durability of symptom relief were assessed in this study.A total of 230 women with adenomyosis who were treated with USgHIFU ablation between January 2007 and December 2013 were retrospectively analyzed. The contrast-enhanced ultrasonography (CEUS) was performed immediately after the treatment to evaluate the ablation effect, and the nonperfused volum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
59
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(68 citation statements)
references
References 22 publications
7
59
2
Order By: Relevance
“…In the multivariate analysis of predictive factors associated with efficacy, we found that the abdominal wall thickness, fibroid volume, fibroid location in the uterus, enhancement time, enhancement intensity, and enhancement rate were independent predictive factors for the treatment outcome after HIFU. Several previous studies confirmed that the abdominal wall thickness, fibroid volume, and fibroid location in the uterus are significantly affected by the sonication dose and thus associated with the efficacy of HIFU . Therefore, we further confirmed that the enhancement rate is a predictive factor for the efficacy of HIFU, independent of conventional predictive factors.…”
Section: Discussionsupporting
confidence: 85%
“…In the multivariate analysis of predictive factors associated with efficacy, we found that the abdominal wall thickness, fibroid volume, fibroid location in the uterus, enhancement time, enhancement intensity, and enhancement rate were independent predictive factors for the treatment outcome after HIFU. Several previous studies confirmed that the abdominal wall thickness, fibroid volume, and fibroid location in the uterus are significantly affected by the sonication dose and thus associated with the efficacy of HIFU . Therefore, we further confirmed that the enhancement rate is a predictive factor for the efficacy of HIFU, independent of conventional predictive factors.…”
Section: Discussionsupporting
confidence: 85%
“…Recently, Liu et al. and Shui et al. reported that common adverse effects after HIFU treatment include pain in the treated region, vaginal discharge, and mild sacral pain.…”
Section: Efficacy and Safety Of Hifu Treatment For Adenomyosismentioning
confidence: 99%
“…The criteria used in most studies can be summarized as follows: (1) premenopausal women of over 18 years of age with no plans for future childbearing [11-16]; (2) significant symptoms related to adenomyosis [11-17]; (3) features of adenomyosis on MR imaging [11,13-16]; (4) adenomyotic lesions greater than 3 cm but less than 10 cm in diameter [11,14]; (5) no evidence of known or suspected extensive pelvic adhesions, such as a history of acute pelvic inflammatory disease, severe pelvic endometriosis, or lower abdominal surgery [12-18]; and (6) body weight of less than 100 kg [16] or abdominal wall thickness of less than 5 cm [17]. …”
Section: Imaging-guided Hifumentioning
confidence: 99%
“…Two articles were excluded because their reported treatment(s) were likely duplicates of those reported in other articles [22,23]. Among the reviewed articles, seven were prospective cohort studies [11,12,14-16,18,21], three were retrospective reviews [13,17,20], and one was a case report [19]. All articles reported the degree of symptom improvement, but only four reported the degree of uterine volume or adenomyotic lesion reduction [11,12,14,17].…”
Section: Literature Reviewmentioning
confidence: 99%